Answer:
The answer is f(x) = x(x-4)
Explanation:
Hi!
1. We can find the equation just by looking at the x-intercepts:
(0,0) and (4,0)
2. We know that if it is an x-intercept, f(x) or y MUST equal 0 meaning that we can substitute f(x) for 0.
x(x-4) = 0
3. Since these (x) and (x-4) multiply to equal 0, we have two possibilities:
-> x = 0
-> x - 4 = 0, or x = 4
4. We can look back at our x-intercepts (step 1) which show that:
x = 0 or x = 4
These are the exact answers that we got in our equation meaning that that is the correct answer.
I hope this helps!